Overcoming exclusion : social justice through education - Mittler, Peter J. (New York : Routledge, 2013)
"In this Collected Works, Professor Peter Mittler brings together nineteen of his key writings in one essential volume, providing a distinctive commentary on some of the most important issues in education over the last thirty years. This unique collection illustrates the development of Professor Mittler's thinking over the course of a long and esteemed career, encompassing his work on the origins of under-achievement, the ways in which obstacles to learning can be understood and overcome and the importance of human rights for all marginalised minorities. It follows the thread of his growing awareness that human development depends on a series of complex interactions between the 'double helix' of nature and nurture. One of the world's most respected and eminent scholars of the field of special needs and inclusive education, Professor Mittler includes chapters from his best-selling books and selected articles from leading journals, providing the reader with a chronological and global perspective on his work and thinking, and the impact it had at and beyond the time of writing"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Inclusive education; Educational equalization; Electronic books